(untitled) (Journal of Misan Researches, 2022)
The research aims to study the features of modernity in the poetry of Hazem Rashke Al-Tamimi as one of the modern poetic voices in contemporary Iraqi literature. There is no doubt that the poetic modernity of the poet constituted a strong obsession that made him transcend the usual limits in the modern Iraqi poem. Through it, he tried to address the renewal and develop the structure of Arabic poetry in form and content. We find the poet through his poetic product, moving away from directness and reporting, and then works to create sophisticated poetic spaces that open up new horizons for the recipient Spacious, deep, creative, and dynamic. Finally, the researchers concluded that the remarkable presence of the poet’s themes of modernity was neither accidental nor arbitrary. Rather, it was deliberate and deliberate, so that he could add a kind of elegance and splendor to the structure of the modernist poem and influence the recipient’s psyche, in addition to his contribution to the idea aimed at it.